LEADERSHIP STYLE, WORK LOAD, MOTIVATION AND STRESS ON THE PERFORMANCE OF NURSES OF CENTRAL SURGICAL INSTALLATIONS OF ORTHOPEDI PROF SOEHARSO HOSPITAL SURAKARTA - Mustika Sari; Kartika Hendra Titisari; Istiatin Istiatin (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2021)
Health services are health efforts that are carried out to achieve the highest possible health status for individuals and the community. This study has purpose to determine and analyse the relationship between leadership style, workload, motivation and stress on nurse performance. This study was conducted at Prof. Soeharso Orthopedic Hospital, Surakarta. This study was conducted using an associative quantitative research with a non-experimental research design, called as a survey design. The population in this study were 45 nurses in the central surgical installation room who worked at Orthopedic Hospital Surakarta. The sampling technique was done using saturated sampling techniques. The instrument used in this study was a questionnaire. The results showed that: 1) leadership style affects employee performance, 2) workload affects employee performance, 3) motivation affects employee performance, and 4) stress affects employee performance at a significance level of 0.05. Keywords: leadership, workload, motivation, stress.